Exploring the health, education and social support needs of individuals diagnosed with SATB2 Associated Syndrome and their families living in Australia - Maryanne Abouharb; Dalal Dawood Baumgartner; Sarah Wilkes-Gillan; Dave Parsons; Lauren Parsons; Iva Strnadová; Elizabeth Emma Palmer; Ryan Chen; Natalie Munro (Rare)
Background: SATB2 Associated Syndrome is a rare genetic neurodevelopmental condition affecting multiple developmental areas including cognition, speech, behaviour and dentition. Currently, a lack of lived experience research exists involving Australian families and individuals diagnosed with SATB2 Associated Syndrome. Aim: The study aimed to enhance understanding of support needs and challenges and access to and experience with health, education, family and community-based support services for individuals diagnosed with SATB2 Associated Syndrome and their families. Method: The study utilised a co-design approach with SATB2 Connect, a not-for-profit organisation supporting Australian families and individuals diagnosed with SATB2 Associated Syndrome. An exploratory cross-sectional online survey employed purposive sampling, targeting individuals diagnosed with SATB2 Associated Syndrome and their families. The analysis encompassed descriptive statistics and content analysis. Result: Out of 32 eligible/invited families, 14 responded representing rural and metropolitan areas across five states/territories. Respondents described challenges faced by individuals diagnosed with SATB2 Associated Syndrome, including communication (100 %), reasoning (100 %), dental care (93 %) and behaviour (86 %). Barriers included limited access to information, therapy and education services. Key therapy obstacles encompassed availability (64 %), multidisciplinary services (57 %) and cost (43 %). Educational barriers included lack of multidisciplinary services (60 %) and educators’ unfamiliarity (40 %) with SATB2 Associated Syndrome. Qualitative analysis supplemented quantitative results, revealing diverse experiences and social support needs. Conclusion: In this first Australian study exploring the health, education and social support needs of individuals diagnosed with SATB2 Associated Syndrome and their families, participants reported accessing health, therapy, education and social supports. Unmet needs were reported related to receiving information about therapy and finding specialist practitioners and support workers with more assistance needed in overcoming therapy and education barriers as well as social support. These findings will drive advocacy, raise syndrome awareness and guide research priorities, potentially enhancing intervention, health and education support services.